Peningkatan Kompetensi Masyarakat Lokal dalam Pemanfaatan Endapan Tras Di Daerah Nagreg Kendan, Kabupaten Bandung, Jawa Barat - Sri Widayati; Dudi nasrudin Usman; Sriyanti Sriyanti; HimawaN Nuryahya; Ike J. Triwardhani (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2019)
Competency enhancement in trass utilization was given to local communities of Nagreg Kendan,Bandung, West Java. This activity was intended to explore the potential of local cummunity indeveloping trass deposit utilization for local economy. This activity is expected to providerecommendation and encouragement for local community to develop entrepreneurship in utilizing andmanaging mineral resources potential. This activity was divided into several parts, they are pre-test,counseling and discussion about trass utilization, and also post-test to evaluate local community’sbasic knowledge. Local community shows good knowledge and enthusiasm of local community indeveloping local economy through trass utilization.